Cadmium activates a mitogen-activated protein kinase gene and MBP kinases in rice - Yeh, C.M. (National Cheng Kung Univ., Tainan (Taiwan)); Hsiao, L.J; Huang, H.J (Plant and cell physiology, 2004)
Mitogen-activated protein kinase (MAPK) pathways are modules involved in the transduction of extracellular signals to intracellular targets in all eukaryotes. In plants, it has been evidenced that MAPKs play a role in the signaling of biotic and abiotic stresses, plant hormones, and cell cycle cues. However, the effect of heavy metals on plant MAPKs has not been well examined. The Northern blot analysis of OsMAPK mRNA levels has shown that only OsMAPK2, but not OsMAPK3 and OsMAPK4, expressed in suspension-cultured cells in response to 100-400 micro M Cd treatments. The OsMAPK2 transcripts increased within 12 h upon 400 micro M Cd treatment. In addition, we found that 42- and 50-kDa MBP kinases were significantly activated by Cd treatment in rice suspension-cultured cells. And 40-, 42-, 50- and 64-kDa MBP kinases were activated in rice roots. Furthermore, GSH inhibits Cd-induced 40-kDa MBP kinase activation. By immunoblot analysis and immunoprecipitation followed by in-gel kinase assay, we confirmed that Cd-activated 42-kDa MBP kinase is a MAP kinase. Our results suggest that a MAP kinase cascade may function in the Cd-signalling pathway in rice.